Neurocognitive effects associated with proprotein convertase subtilisin-kexin type 9 inhibitor use: a narrative review. (March 2021) - Yuet, Wei C.; Ebert, Didi; Jann, Michael
Neurocognitive adverse events have been observed with the widespread use of 3-hydroxy-3-methylglutaryl-CoA reductase inhibitors or "statins, " which reduce low-density lipoprotein cholesterol (LDL-C) levels and subsequently cardiovascular risk. The United States Food and Drug Association directed manufacturers of proprotein convertase subtilisin-kexin type 9 (PCSK9) inhibitors to monitor for neurocognitive adverse events due to their potent effects on LDL-C reduction, which is a proposed mechanism for neuronal cell dysfunction. Other proposed mechanisms for PCSK9 inhibitor-associated neurocognitive adverse events include N-methyl-d -aspartate receptor modulation, dysregulation of lipid and glucose metabolism, and patient-specific risk factors for cognitive impairment. The purpose of this narrative review article is to describe the proposed mechanisms, incidence of neurocognitive adverse events from phase II and III trials for PCSK9 inhibitors, neurocognitive assessments utilized in clinical trials, and clinical implications. Given the increasing prevalence of PCSK9 inhibitor use and the neurocognitive adverse events observed with prior lipid-lowering therapies, clinicians should be aware of the risks associated with PCSK9 inhibitors, especially when therapy is indicated for patients at high risk for cardiovascular events. Overall, the incidence of PCSK9 inhibitor-associated neurocognitive appears to be uncommon. However, additional prospective studies evaluating cognitive impairment may be beneficial to determine the long-term safety of these agents.